ANALISIS TERBITNYA SERTIPIKAT TANAH ATAS NAMA LIBRECHT FRANS WATTIMENA BERDASARKAN GAMBAR SITUASI No. 41/D/77 BIDANG TANAH ATAS NAMA MATHEOS HUKUM - MEITRI CITRA WARDANI; Lanny Kusumawati; Suhariwanto Suhariwanto (Perpustakaan Universitas Surabaya, 2018)
The purpose of writing this scientific journal is as a requirement for graduation and obtaining a law degree at the Faculty of Law of the University of Surabaya. Practical Objectives of the writing of this thesis to be able to know Is the issuance of land titles certificate by the Land Office without based on the picture of the situation as the physical data of the land is justified according to law. Librecht Frans Wattimena as a registrant for the land area of 323 M2 and the holder of the land title certificate, in conjunction with the provisions of article 32 paragraph (2) of PP. 24 of 1997, that the guarantee of legal certainty over the certificate is only given to the registrant with good intentions. Librecht Frans Wattimena as a registrant whose intention is not good because registering the land without the certificate of land history, then the certificate is legal defect, the certificate can be applied for the cancellation. Based on the description as mentioned above can be explained that the issuance of land titles certificates by the Land Office without being based on the picture of the situation as physical data of the land is not justified by law, because the certificate is no letters or there is but not in accordance with the truth, Measuring which is the picture of the situation is in the hands of Matheos Law. The effort that must be taken by Matheos Law is to file a lawsuit against the certificate to the State Administrative Court.